Extreme Hydrometereological Events in Costa Rica from the Perspective of Adaptation to Climate Change - Retana, José (2012)
The indirect effects from a Caribbean hurricane, low pressure systems and cold fronts, are the Extreme Hydrometeorological  Events (EHE) that cause greater impacts due to excessive rains in Costa Rica. Hurricanes are the events that individually generate more precipitation. The highest frequency is between september and november and its impacts are in the Pacific side. Cold fronts are the most common phenomena.  Usually, they are concentrated between december and january and impact the northern and the Caribbean regions. The low pressure system occurs between April and November and its effects can be felt in the Caribbean and the Pacific. Cold fronts tend to decrease.  That means progressive drier scenarios in the Caribbean and Northern Region between november and february. The low pressure systems and hurricanes in the Caribbean, also tend to decrease, but the trend of the past 30 years shows a slight increase. These features of the EHE should be the basis for adaptation strategies.